2003
DOI: 10.1002/em.10164
|View full text |Cite
|
Sign up to set email alerts
|

Arsenite induces delayed mutagenesis and transformation in human osteosarcoma cells at extremely low concentrations

Abstract: Arsenite is a human multisite carcinogen, but its mechanism of action is not known. We recently found that extremely low concentrations ( Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(40 citation statements)
references
References 80 publications
1
39
0
Order By: Relevance
“…An improved comet assay using Fpg glycosylase as a probe provided new evidence that arsenite levels equivalent to those associated with clinical pathology (1 to 500 nM) were indeed able to cause rapid (1-to 6-h) formation of DNA lesions, such as 8-oxoguanine and AP sites (55,59,69). For arsenic mutagenesis and tumorigenesis, Mure et al (45) showed that human osteosarcoma TE85 cells cultured with 100 nM sodium arsenite for 20 generations (3 weeks) increased the mutation frequency at the HPRT locus three-to fivefold, and after 30 generations (5 weeks), phenotypically transformed cells could be detected. Mutations were induced by arsenite but not by methyl arsenic derivates (45).…”
Section: Discussionmentioning
confidence: 99%
“…An improved comet assay using Fpg glycosylase as a probe provided new evidence that arsenite levels equivalent to those associated with clinical pathology (1 to 500 nM) were indeed able to cause rapid (1-to 6-h) formation of DNA lesions, such as 8-oxoguanine and AP sites (55,59,69). For arsenic mutagenesis and tumorigenesis, Mure et al (45) showed that human osteosarcoma TE85 cells cultured with 100 nM sodium arsenite for 20 generations (3 weeks) increased the mutation frequency at the HPRT locus three-to fivefold, and after 30 generations (5 weeks), phenotypically transformed cells could be detected. Mutations were induced by arsenite but not by methyl arsenic derivates (45).…”
Section: Discussionmentioning
confidence: 99%
“…Control parental HOS cells were cultured in α-MEM medium containing 5 or 10% FBS. Two types of As-treated cells were generated by incubating cells with a low dose of arsenite (0.1 µM), as previously described [13,14]. Cells designated here as As-8w-HOS were cells that were chronically exposed to NaAsO 2 for 8 weeks.…”
Section: Cell Culturementioning
confidence: 99%
“…As previously described, HOS cell transformation occurred only after 8 weeks of low-dose arsenite treatment [13,14]. Ferritin levels in the parental HOS cells were measured as a function of time of exposure to 0.1 µM arsenite.…”
Section: Changes In Ferritin Levels During the Process Of As-mediatedmentioning
confidence: 99%
See 2 more Smart Citations